2005
DOI: 10.1007/s00415-005-0624-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reactivity and dynamic autoregulation in nondemented patients with CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy)

Abstract: Reduced cerebrovascular reactivity has been reported in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), and the measurement has been suggested as a useful surrogate marker of disease progression. Previous studies have not determined whether cerebral autoregulation is also impaired. We measured dynamic cerebral autoregulation and carbon dioxide reactivity in 24 nondemented CADASIL patients and 20 controls, using transcranial Doppler ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…This conforms to the reduction of blood flow in the peripapillary retina demonstrated by scanning laser Doppler flowmetry (27). Furthermore, the reduced cerebral blood flow in CADASIL is associated with increased distal cerebrovascular resistance (28) and it can be decreased by administration of acetazolamide (29) or carbon dioxide (28,30). In addition, it was recently shown that CADASIL patients have enhanced maximal constriction response to angiotensin II in the resistance arteries (31).…”
Section: Biological Functions Of the Identified Proteins And Their Posupporting
confidence: 71%
“…This conforms to the reduction of blood flow in the peripapillary retina demonstrated by scanning laser Doppler flowmetry (27). Furthermore, the reduced cerebral blood flow in CADASIL is associated with increased distal cerebrovascular resistance (28) and it can be decreased by administration of acetazolamide (29) or carbon dioxide (28,30). In addition, it was recently shown that CADASIL patients have enhanced maximal constriction response to angiotensin II in the resistance arteries (31).…”
Section: Biological Functions Of the Identified Proteins And Their Posupporting
confidence: 71%
“…In experimental investigations, impaired cerebral vasoreactivity in a transgenic mouse model of CADASIL was observed [13]. Also clinical studies on CADASIL patients demonstrated abnormal vasoreactivity [9,26] and a reduced cerebral blood flow [20,23] in the course of the disease. Integrin subunit β1 as a part of α1β1 and α5β1 integrin receptors is involved in vasoconstriction and transfer of signals originating from ECM and regulating permeability of calcium channels on VSMCs and myocytic voltage value.…”
Section: Discussionmentioning
confidence: 98%
“…14 Another transcranial Doppler study showed only reduced basal blood flow velocity, but preserved increase in response to CO 2 and to blood pressure reduction. 26 A reduction of basal blood flow in CADASIL patients has also been described in cerebral white matter with PET 27 and in retinal vessels. 28 The reduced endothelial function in smaller resistance arteries that we showed in this study may be a key element in the development of ischemic lesions in CADASIL patients especially in the brain, which is the organ with the highest degree of autoregulation of blood flow.…”
Section: Stenborg Et Al Impaired Endothelial Function In Cadasil Patimentioning
confidence: 93%